WILLIAM MAKEPEACE THACKERAY: IRONIC CONTEXT OF HIS “KYIV TEXT” - Mykhed , T. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the analysis of the parody ballad by W. M. Thackeray "The Legend of St. Sophia of Kioff" (1839). An attempt was made to indicate the source of information about Kyiv, which could be found in Jane Porter’s historical novel "Thaddeus of Warsaw", written according to the testimonies of Polish emigrants. The ballad is interpreted as a traditional for English oral and written literature genre, which has acquired formal signs of printed text. All these signs are present in Thackeray's ballad, including the division into chapters, a functionally significant paratext, topical historical and cultural allusiveness, satirical-defamatory pathos, polemics. "Kyiv text" in Thackeray’s poem is modeled according to the genre conventions of the ballads about St. George, stating an informative narrative with a programmed and incessant general message. Thackeray creates the image of Kyiv in the traditions of utopian literature, calling it a real paradise. Kyiv happy residents became victims of envious neighbors, whose ethnographic and religious affiliation is absurdly mottled. Thackeray does not hold on to the historical truth, forming a fictional space, markers of which are stereotypes of romantic literature topos, comparisons, the allusion to the works and the style of Byron, Hoffman and other romantics. Irony becomes the defining ideological and aesthetic dominant of Thackeray’s ballad about the confrontation between the Kyivans and Cossack invaders, which, marked by intertext, forms the distance of the narrator from the text, inducing the reader to form his own ironic perception of both the artistic world of the work and of the reality.__________References• Tekkerej U. M. Tvorchestvo. Vospominanija. Bibliograficheskie izyskanija. Sost. E. Geniieva. – M.: Knizhnaja palata, 1989. – 488 s.• Catalan, Zelma. The Politics of Irony in Thackeray’s Mature Fiction: Vanity Fair, Henry Esmond, The Newcomes.Sofia (Bulgaria), 2010, 250 pp.• Fox, Adam. Remembering the Past in Early Modern England: Oral and Written Tradition.” Transactions of the Royal Historical Society 9 (1999): pp. 233-256.• Ganev, Robin. Songs of Protest, Songs of Love: Popular Ballads in Eighteenth-Century Britain. Manchester, UK: Manchester University Press, 2009, 256 pp.• Monsarrat, Ann. An Uneasy Victorian: Thackeray the Man, 1811–1863. London: Cassell, 1980, 504 pp.• Shillingsburg, Peter. William Makepeace Thackeray: A Literary Life. Basingstoke: Palgrave, 2001, 177 pp.• Thackeray W. M. The Legend of St. Sophia of Kioff. Режим доступу https://www.poemhunter.com/poem/the-legend-of-st-sophia-of-kioff/comments/ Балада Теккерея у нашому перекладі скрізь цит. за цим джерелом.• Trollope, Anthony. Thackeray. English Men of Letters series edited by John Morley. London: Macmillan & Co., 1879. Project Gutenberg eBook #18645 prepared by Barbara Tozier, Bill Tozier, Lisa Reigel, and the Project Gutenberg Online Distributed Proofreading Team. June 21, 2006. Web. 8 August 2014.
Keywords: Thackeray, ballad, irony, Kyiv text, St. Sophia